(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The present study is concerned with the role of income tax in implementing economic goals in Iraq and treating the problems and pitfalls in the Iraq economy. The study also aims at investigating the role of income tax in attracting promising favorite effects into economy. The study was performed on data covering the period (2003 - 2012) with respect to the variables of (income tax, oil profits) as independent variables and (private consuming expenditure, private investmental expenditure, and standard figure of prices) as dependent variables. To analyze these data, a number of statistical descriptive and analytical techniques were used such as (percentage, standard variance, mediums, F test, T test and SPSS). It has been concluded that income tax has only a weak role in supporting economic goals in Iraq due to the entire exclusive reliance on oil. The researcher recommends the reform and systemization of income tax so as to enhance national economy and using it as another source for Iraq’s budget instead of depending on oil only which is yoked to international external factors.